PERCEPTION OF BUSINESS ENGLISH COMMUNICATION STUDENTS TOWARDS ONLINE SHOPPING ON TIKTOK SOCIAL MEDIA - M, Musdalifa; Luhriyani, Seny; Novia, Lely (Universitas Negeri Makassar, 2023)
TikTok is a social media platform that is popular around the world. The TikTok app allows users to create, share, and watch short videos that last 15 to 60 seconds. TikTok introduced a new feature, TikTok shop, which is an e-commerce feature that allows TikTok users to sell and buy products directly in the TikTok application. Research data analysis uses descriptive qualitative and is collected through questionnaires and interviews. This research was conducted at the Faculty of Language and Literature, Business English Communication study program. In this study, the object of research was Business English Communication study program students totaling 5 people. The results of this study indicate that the perception of the influence and effectiveness of TikTok social media for students is easy to access, implicit purchases made, inspiration and product information special offers and discounts, can save time. The obstacles faced by students when shopping online at TikTok are slow delivery of products and fraudulent purchases but do not reduce the desire of students to shop online through TikTok because of the many benefits that can be obtained.